Synthesis, Crystal Structure, and DFT Study of Two New Dinuclear Copper(I) Complexes Bearing Ar‐BIAN Ligands Functionalized with NO2 Groups. Issue 30 (13th July 2020) - Outis, Mani; Rosa, Vitor; Laia, César A. T.; Lima, João Carlos; Barroso, Sónia; Carvalho, Ana Luísa; Calhorda, Maria José; Avilés, Teresa
Abstract : Two new bis(aryl‐imino)‐acenaphthene, Ar‐BIAN (Ar = 2, 4, 6‐trimethylphenyl = mes) ligands, bearing the NO2 group in the naphthalene moiety of the iminoacenaphthene at para‐ (5‐NO2 ) and meta‐ (4‐NO2 ) position, of formulations 1, 2‐bis(mes‐imino)‐5‐nitroacenaphthene, 1, and 1, 2‐bis(mes‐imino)‐4‐nitroacenaphthene, 2, were synthesized. Their respective dinuclear iodide bridged copper(I) complexes [Cu2 (µ‐I)2 (mes‐BIAN‐5‐NO2 )2 ], 3 and [Cu2 (µ‐I)2 (mes‐BIAN‐4‐NO2 )2 ], 4, were obtained in good yields by treatment with an equimolar amount of CuI. All compounds were characterized by elemental analysis, single‐crystal X‐ray diffraction, 1 H‐NMR, 13 C‐NMR, FTIR, UV/Vis spectroscopy. DFT calculations helped to understand the different molecular structure observed in the crystals of 3 and 4 and the determining role of packing forces. TDDFT revealed that the absorption bands in the visible were essentially MLCT (Metal to Ligand Charge Transfer), with some n→π* character (intra ligand). The shift to the red compared to the spectrum of the Cu(I) complex analogue without the NO2 group, [Cu2 (µ‐I)2 ](mes‐BIAN)2 ], 6, could be explained by the stabilization of the ligand unoccupied π* orbitals in the presence of NO2 . Abstract : Cu(I) complexes [Cu2 (µ‐I)2 (LL)2 ] bearing two new bis(aryl‐imino)‐acenaphthene (LL) ligands, each with one NO2 group in the naphthalene moiety were synthesized. The different arrangements of the Cu2 (µ‐I)2 cores, one planar and the other puckered, were assigned to packing forces, based on the X‐ray structures and DFT calculations. Absorption bands in the visible were essentially MLCT.